The Association of Predeployment and Deployment-Related Factors on Dimensions of Postdeployment Wellness in U.S. Military Service Members. Issue 2 (November 2013) - Bagnell, Melissa E.; LeardMann, Cynthia A.; McMaster, Hope S.; Boyko, Edward J.; Smith, Besa; Granado, Nisara S.; Smith, Tyler C.
Purpose: To assess the effects of predeployment and deployment-related factors on dimensions of wellness following deployment. Design: Prospective longitudinal study. The dependent variable was dimensions of wellness. Independent variables were measured in terms of modifiable, nonmodifiable, and military factors, such as sex, race/ethnicity, service branch, smoking status, and combat experience. Setting: A large military cohort participating in the Millennium Cohort Study. Subjects: Included 10, 228 participants who deployed in support of the operations in Iraq and Afghanistan. Measures: Dimensions of wellness were measured by using standardized instruments assessing self-reported physical health, mental health, and stress. Covariates were measured by using self-reported and electronic data. Analysis: Factors of postdeployment wellness were assessed by using ordinal logistic regression. Results: Most participants (78.7%) were categorized as "moderately well" post deployment. Significant modifiable predeployment predictors of postdeployment wellness included normal/underweight body mass index (odds ratio [OR] = 1.72, p < .05). Military factors significantly associated with wellness included not experiencing combat (OR = .56, p < .05), member of Air Force (OR = 2.02, p < .05) or Navy/Coast Guard (OR = 1.47, p < .05), and combat specialist occupation (OR = 1.22, p < .05). Conclusion: Multiple modifiable factors associated with postdeployment wellness were identified, which may help inform medical and military leadership on potential strategies to ensure a well force. Those trained in combat roles were more likely to be well post deployment though this apparent benefit was not conferred onto those reporting combat experiences.